Uma comunicologia engajada: aproximações entre Vilém Flusser e Paulo Freire sobre processos comunicativos aplicados à educação - Rodrigues, Gustavo Uliana (2023)
This research proposes to outline the theoretical approaches on Vilém Flusser's theory of communicology and Paulo Freire's pedagogical proposal. To do so, it presents and analyzes Vilém Flusser's theory of communication, highlighting the relevant texts written on education and its application at Fundação Armando Alvares Penteado and Paulo Freire's pedagogical theory. For this, it contextualizes the authors in the political and social historical scenario, aiming to highlight the cultural and subjective determinants that allowed them to elaborate their projects aimed at communication and education. The objective of this research is to trace the common points in their theories about approaches to problematizing, critical, reflective and emancipatory education. This happens through the concepts of intersubjectivity, dialogue as a problematizing dialectical process, multidisciplinarity, awareness, contextualization and the proposal of teaching as a transformative method. The analyses, alignments and criticisms of the authors' theoretical conceptions will form the methodological basis of this study. The research will be theoretically based on the concepts and texts on education written by Vilém Flusser and also on his conception of communicology, having as reference the Arquivo Vilém Flusser São Paulo (sponsored by Pontifícia Universidade Católica de São Paulo), the educational proposal of Paulo Freire, joining the contributions of Norval Baitello Junior and authors related to the theme this subject, as well as the flusserian project at Fundação Armando Alvares Penteado